Early B lymphocyte subsets in blood predict prognosis in sepsis - Sun, Yingqian; Lu, Yan; Pan, Xinling; Zhang, Chengliang; Wang, Liang; Zhang, Longyi (Frontiers in Immunology, 2024)
Background: B lymphocytes play a key role in immunosuppression. This study investigated the prognostic value of B cell subsets in sepsis.Methods: Flow cytometry was used to assess peripheral B cell subsets from patients with sepsis on the first and seventh days following admission, as well as 111 healthy controls. The patients were divided into survivors and non-survivors, based on 28-day prognosis.Results: The analysis showed abnormal distribution and selective depletion of B cells and its subsets in the early stages of sepsis. On day 1, compared with survivors, non-survivors showed significant decreases in the proportion and absolute count of transitional (Tr) B cells, reductions in the proportion of CD5 + B cells, and increases in the proportion of double-negative (DN) B cells. On day 7, the proportions and absolute counts of Tr and CD5 + B cells significantly decreased whereas the proportions of DN B cells significantly increased in non-survivors. Ninety-four survivors and 15 nonsurvivors were included in our paired-sample rank-sum test. Compared to day 1, only the survivors showed significant increases in absolute B, Tr B, and CD5 + B cell counts by day 7. Multivariate Cox regression analysis showed that the proportion of DN B cells on day 1 (hazard ratio = 1.092 [95% confidence interval: 1.035-1.152], P = 0.001) was a risk factor for mortality, and Kaplan-Meier survival curve analysis showed that patients with proportions of DN B cells > 11.81% on day 1 had poorer prognoses. Receiver operating characteristic curve analysis showed that B cell subset parameters could predict mortality (area under the receiver operating characteristic curve [AUC], 0.741) and enhanced the prognostic value of the Acute Physiology and Chronic Health Evaluation II score (AUC, 0.840).Conclusion: Our study revealed that deficiencies of B, Tr B, and CD5 + B cells, as well as a persistent increase in the proportion of DN B cells, were associated with poor prognosis-and that B cell subsets showed predictive value to mortality. These results provide new insights into the roles of B cell subsets in sepsis, as well as ways to better manage its progression and predict its course.